Secondary battery, electrode for secondary battery, and electrolyte for secondary battery

The use of an Mg-based alloy with an LPSO structure in secondary batteries addresses the environmental and safety issues of carbon/graphite use, providing a compact, efficient, and safe battery solution for carbon neutrality.

JP2025004328APending Publication Date: 2025-01-15TECH ON DEMAND LLC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023103939
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-26
Publication Date
2025-01-15

AI Technical Summary

Technical Problem

Existing secondary batteries face challenges in achieving carbon neutrality due to the use of carbon and graphite in their negative electrodes, which are not environmentally friendly, and they suffer from dendrite formation leading to reduced charging efficiency and safety issues.

Method used

The use of an Mg-based alloy with a Long Period Stacking Ordered (LPSO) structure as a component in the secondary battery, which includes a lightweight Mg-Li alloy matrix, avoids carbon and graphite, and employs a solid electrolyte to prevent dendrite formation and ignition risks.

Benefits of technology

This approach results in a small, lightweight secondary battery suitable for achieving carbon neutrality with improved charging efficiency and safety, maintaining high discharge capacity even after repeated cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025004328000001_ABST
    Figure 2025004328000001_ABST
Patent Text Reader

Abstract

To provide a small, lightweight secondary battery that does not use carbon or graphite and is suitable for achieving carbon neutrality.SOLUTION: In a secondary battery 1 according to the present invention, at least one secondary battery component 3 contains a Mg-based alloy having an LPSO structure (Long Period Stacking Ordered Structure). The secondary battery is preferably a LiB (lithium ion battery). The secondary battery component is preferably an electrode 5 and / or an electrolyte 7. The Mg-based alloy is preferably a Mg-Li alloy, and preferably contains a transition metal element and a rare earth element.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a secondary battery, an electrode for a secondary battery, and an electrolyte for a secondary battery. [Background technology]

[0002] Known devices that use chemical reactions to extract electrical energy include primary batteries, secondary batteries, rechargeable batteries, and fuel cells. A battery is a system that reacts an oxidant with a reductant using electrons and ions as intermediaries, and directly converts the Gibbs free energy released during the reaction into electrical energy.

[0003] Primary batteries are discarded because they cannot be recharged or the efficiency of recharging is low once they have been used up, while secondary batteries can be discharged and then recharged. When discharging a battery, the oxidizing agent at the positive electrode receives electrons and is reduced, and the reducing agent at the negative electrode releases electrons and is oxidized.

[0004] However, in the case of secondary batteries, repeated charging and discharging causes metal elements to precipitate in the form of resin (dendrite) on the negative electrode, which poses fatal problems in terms of charging efficiency, reliability, and safety.

[0005] In response to this, Patent Document 1 discloses an invention relating to a lithium-ion battery in which carbon and graphite capable of absorbing and releasing lithium (metal) are used as negative electrode materials.

[0006] Meanwhile, with the recent widespread use of portable devices and electric vehicles, there is an increasing demand for secondary batteries that can be made smaller and lighter.

[0007] Among battery performance indicators, increasing the energy density of a battery is important. There are two main ways to indicate the energy density of a battery. One is volumetric energy density (Wh / l), which is used as an indicator of battery miniaturization. The other is gravimetric energy density (Wh / kg), which is used as an indicator of battery weight reduction.

[0008] The energy density of a battery is determined mainly by the active materials in the positive and negative electrodes that make up the power generating elements. The electrolyte and separator are also important elements. Furthermore, the size and weight of the metal case that houses the power generating element are also being reconsidered as important elements. Patent Document 2 discloses an invention relating to a lithium ion battery in which the metal case is made of an Mg-Li alloy to reduce the weight, thereby improving the weight energy density of the battery as a whole. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] Japanese Patent Application Publication No. 7-142089 [Patent Document 2] JP 2001-283796 A Summary of the Invention [Problem to be solved by the invention]

[0010] In recent years, various weather disasters have occurred both in Japan and overseas. Although it is not easy to clarify the relationship between individual weather disasters and climate change issues, it is expected that the risk of heavy rain and extreme heat will increase further in the future due to climate change. Greenhouse gases, which cause climate change, are said to be emitted as a result of economic activities and daily life.

[0011] In response to this, the Japanese government declared in October 2020 that it would aim to achieve carbon neutrality, that is, to reduce greenhouse gas emissions to zero overall by 2050. Carbon neutrality means reducing CO2 emissions to zero by canceling them out with carbon negative factors (CO2 absorption by forests, etc.). To achieve carbon neutrality, no one is unrelated, and all actors are called upon to work toward it.

[0012] However, the inventions disclosed in Patent Documents 1 and 2 are both premised on the use of carbon and graphite in the negative electrode. In order to achieve the targets set by the government while taking into account regulations on greenhouse gas emissions during the manufacture and disposal of secondary batteries (carbon footprint regulations) and regulations on recycling, it is desirable to be able to provide secondary batteries using an approach other than the use of carbon and graphite in the negative electrode.

[0013] An object of the present invention is to provide a small, lightweight secondary battery that does not use carbon or graphite and is suitable for achieving carbon neutrality. [Means for solving the problem]

[0014] As a result of intensive research into solving the above problems, the present inventors have found that the above object can be achieved by using an Mg-based alloy having an LPSO structure (Long Period Stacking Ordered Structure) for a battery component of a secondary battery, and have completed the present invention. Specifically, the present invention provides the following.

[0015] A first aspect of the present invention provides a secondary battery in which at least one secondary battery component contains an Mg-based alloy having an LPSO structure (Long Period Stacking Ordered Structure).

[0016] According to the first aspect of the invention, a lightweight Mg-based alloy matrix is ​​used, making it possible to provide a small, lightweight secondary battery that does not use carbon or graphite and is suitable for achieving carbon neutrality.

[0017] A second feature of the invention is the first feature of the invention, which provides a secondary battery that is a LiB (lithium ion battery).

[0018] According to the second aspect of the invention, a small and lightweight secondary battery can be provided.

[0019] A third aspect of the present invention provides a secondary battery according to the first or second aspect of the present invention, wherein the secondary battery constituent members are electrodes and / or an electrolyte.

[0020] According to the third aspect of the invention, a structure having an LPSO structure (hereinafter also referred to as "LPSO structure") is composed of a Mg layer and multiple LPSO layers, and can be used as a site for intercalation of Li ions. Conventional organic polymer electrolytes have a risk of ignition, but when the electrolyte is an Mg-Li alloy having an LPSO structure, it is a solid electrolyte and there is no risk of ignition.

[0021] Below, we explain in detail how the LPSO structure can be used as a site for Li ion intercalation.

[0022] First, we compare the crystal structure of lithium manganese oxide, which is used as the positive electrode active material in full-intercalation LiB (lithium ion battery), with the ionic radius of lithium.

[0023] Spinel-type oxide Li x Mn2O4 (0≦x≦1) has diffusion channels for lithium ions and sites for storing lithium ions, and lithium ions are moved into and out of the lattice positions while maintaining the lattice structure. At that time, the valence of the manganese ions changes between +3.5 when x=1 and +4 when x=0 due to charge compensation.

[0024] The oxide Mn2O4 (x=0), which consists of a +4-valent manganese ion and a lithium vacancy (hole), is called λMnO2 (the space before the Mn means that the site that would accommodate the lithium ion is a hole), and is used as an electrode material in lithium-ion secondary batteries.

[0025] In addition, both LiMn2O4 and crystals (λMnO2) obtained by removing Li from LiMn2O4 have a spinel crystal structure. Regarding the hydroxyl group density as an index of the ion exchange capacity of spinel-type manganese oxide λMnO2, Non-Patent Document 1 discloses that although there is some variation in the change in lattice constant depending on the preparation method of LiMn2O4, the values ​​are roughly similar as follows: Preparation method 1) LiMn2O4:0.8226nm→λMnO2:0.8038nm Preparation method 2) LiMn2O4:0.8251nm→λMnO2:0.8028nm

[0026] On the other hand, the ion radius of Li is estimated to be 0.145 nm and the diameter is estimated to be 0.29 nm, which is about 36% of the lattice constant of λMnO2, which is 0.80 nm. In other words, if the crystal has a framework structure with a lattice constant larger than the diameter of the Li ion, full intercalation is possible.

[0027] Next, we compare the lattice spacing of the LPSO structure with the diameter of the Li ion.

[0028] The LPSO structure is a structure that results from the formation of a stacking order by introducing periodic stacking faults into the original hcp structure (hexagonal close-packed structure). For example, the layer spacing (lattice spacing is twice the layer spacing) of the stacking order including the 24R (orthorhombic crystal structure) periodic structure is 0.27 nm, and the lattice spacing of the c-axis is estimated to be approximately 0.54 nm. The size ratio of the lattice spacing of the c-axis, 0.54 nm, to the diameter of a Li ion, 0.29 nm, is estimated to be approximately 54%. In other words, a comparison of the lattice spacing and the ion diameter shows that Li ions can be sufficiently intercalated within the crystal lattice of the LPSO structure.

[0029] From the above, according to the third aspect of the invention, the LPSO structure is composed of Mg layers and multiple LPSO layers, and can be used as a site for intercalation of Li ions.

[0030] A fourth aspect of the present invention provides a secondary battery according to any one of the first to third aspects of the present invention, wherein the Mg-based alloy is an Mg-Li alloy.

[0031] According to the fourth aspect of the invention, a structure having an LPSO structure precipitates surrounding crystal grains of lightweight α-Mg (hcp structure: hexagonal close-packed structure or close-packed hexagonal lattice structure) and β-Mg (Mg-Li alloy: bcc structure: body-centered cubic lattice structure), and the β-Mg becomes a deformation absorption site.

[0032] A fifth aspect of the present invention is the secondary battery according to any one of the first to fourth aspects, wherein the Mg-based alloy contains a transition metal element and a rare earth element.

[0033] According to the fifth aspect of the present invention, a secondary battery can be provided in which the interlayer distance of the LPSO can be controlled by the type and amount of a transition metal element and / or a rare earth element added to Mg or an Mg-Li alloy.

[0034] For example, in the phase where zinc (Zn) and yttrium (Y) are concentrated in the Mg crystal, it is estimated that there are gaps where ions that contribute to the battery reaction can reside, and there are lattice defects that are responsible for ionic conduction. In other words, ionic conduction in LPSO is possible from the viewpoint of defect formation.

[0035] A sixth aspect of the invention is the invention according to any one of the first to fifth aspects, providing a secondary battery containing an Mg-based high-entropy alloy and / or an Mg-Li-based high-entropy alloy, in which the Mg-based alloy has the LPSO structure in at least a part of its structure.

[0036] According to the sixth aspect of the present invention, a secondary battery having strength characteristics suitable for use at high temperatures can be provided.

[0037] A seventh aspect of the present invention provides an electrode for a secondary battery, which contains an Mg-based alloy having an LPSO structure (Long Period Stacking Ordered Structure).

[0038] An eighth aspect of the present invention provides an electrolyte for a secondary battery, which contains an Mg-based alloy having an LPSO structure (Long Period Stacking Ordered Structure). Effect of the Invention

[0039] According to the present invention, it is possible to provide a small, lightweight secondary battery that does not use carbon or graphite and is suitable for achieving carbon neutrality. [Brief description of the drawings]

[0040] [Figure 1] FIG. 1 is a schematic diagram showing an outline of a cross-section of a secondary battery (lithium ion battery, LiB) according to a first embodiment of the present invention. [Diagram 2] Figure 2(A) is a schematic diagram of the state of crystal grains in an Mg-Li alloy, and Figure 2(B) is a STEM-HAADF (scanning transmission electron microscope - high-angle annular dark-field) image of the LPSO structure. [Diagram 3] 3 is a diagram showing the results of structural observation of the Mg-Li-YZ alloy according to the first embodiment of the present invention by a scanning transmission electron microscope (STEM), in which Y represents a transition metal element and Z represents a rare earth element. [Figure 4] Fig. 4 shows elemental mapping of Mg, Y, and Z by energy dispersive X-ray spectroscopy (EDS mapping) for the LPSO structure contained in the Mg-Li-YZ alloy. (c) shows the rare earth element Y (yttrium), and (d) shows the transition metal element Cu (copper). [Diagram 5]FIG. 5 is a STEM-HAADF image of an LPSO structure obtained by casting a 78.5%Mg-18.0%Li-1.5%Cu-2.0%Y (yttrium) alloy (% indicates atomic percent) according to the first embodiment of the present invention. [Figure 6] FIG. 6 is an enlarged view of a portion of FIG. [Figure 7] FIG. 7 is a STEM-HAADF image of an LPSO structure obtained by casting a 78.5% Mg-18.0% Li-1.5% Ni-2.0% Y (yttrium) alloy (% indicates atomic percent) according to the first embodiment of the present invention. [Figure 8] FIG. 8 is a STEM-HAADF image of an LPSO structure obtained by subjecting a 78.6%Mg-18.0%Li-0.7%Cu-0.7%Ni-2.0%Y (yttrium) alloy (% indicates atomic percent) according to the first embodiment of the present invention to heat treatment at 400° C. for 100 hours. [Figure 9] FIG. 9 is a schematic diagram comparing the crystal framework structure and ion size of lithium manganate used as a positive electrode active material in a full-intercalation type LiB (lithium ion battery). [Figure 10] 10 is a diagram showing the battery characteristics when the Mg-Li-YZ alloy having the LPSO structure is applied to the negative electrode of the solid-state lithium-ion battery according to the first embodiment of the present invention, where Y represents a transition metal element and Z represents a rare earth element. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0041] Hereinafter, examples of preferred embodiments for carrying out the present invention will be described with reference to the drawings. More specifically, as a representative example of a small and lightweight secondary battery, a case where the secondary battery is a lithium ion battery will be described. Note that these are merely examples, and the technical scope of the present invention is not limited to these. For example, the secondary battery is not limited to being a lithium ion battery, and the present invention is not limited to the following embodiments with respect to each member constituting the secondary battery, and can be carried out with appropriate modifications within the scope of the object of the present invention.

[0042] [Secondary battery 1] 1 is a schematic diagram showing an outline of a secondary battery (lithium ion battery) 1 as viewed from the front. The secondary battery 1 includes at least a case 2 and battery components 3. The battery components 3 include at least a positive electrode 4, a negative electrode 5, a separator 6, and an electrolyte 7.

[0043] This figure shows a secondary battery using a liquid electrolyte, but when a solid electrolyte is used, the separator 6 is not necessary. The embodiment using a solid electrolyte is also a secondary battery according to the present invention.

[0044] In a lithium-ion battery, as current moves due to an external charging electrode (not shown), lithium ions escape from the crystal structure of the positive electrode 4 into the electrolyte 7 and are inserted between the crystal layers of the negative electrode 5 (charging reaction). Meanwhile, lithium ions escape from between the crystal layers of the negative electrode 5 into the electrolyte 7 and are inserted into the crystal structure of the positive electrode 4, allowing current to be extracted to an external circuit (not shown) and causing a load (not shown) to do work (discharging reaction).

[0045] The general reaction formula for a lithium-ion battery is as follows: Positive electrode: Li (1-x) MO2+ xLi + +xe - ←→ LiMO2 (M is a metal element (e.g. Ni, Mn, Co).) Negative electrode: Li x C ←→ C + xLi + +xe - Whole battery: Li (1-x) MO2+ Li x C ←→ LiMO2+ C

[0046] [Case 2] The casing 2 houses the battery components 3 (e.g., a positive electrode 4, a negative electrode 5, a separator 6, and an electrolyte 7) in a predetermined positional relationship. The casing 2 is not particularly limited and may be a casing 2 for a secondary battery of the prior art. By providing the casing 2, the various battery components 3 can be housed in a predetermined positional relationship that allows the secondary battery 1 to operate appropriately. Note that if the casing 2 is made of an Mg alloy, it is preferable because it is lightweight and allows the secondary battery 1 to be small and lightweight.

[0047] [Battery components 3] The battery components 3 include at least a positive electrode 4 , a negative electrode 5 , a separator 6 , and an electrolyte 7 .

[0048] (positive electrode 4) The positive electrode 4 contains a lithium transition metal composite oxide. During charging, lithium ions are released from the crystal structure of the positive electrode 4 into the electrolyte 7 as current flows, and during discharging, lithium ions are inserted into the crystal structure of the positive electrode 4.

[0049] For example, lithium transition metal composite oxides include lithium cobalt oxide (LiCoO2), lithium nickel cobalt aluminum oxide (LiNi 0.8 Co 0.15 Al 0.05 O2), lithium nickel manganese cobalt oxide (LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O2), lithium manganese oxide (LiMn2O2), lithium iron phosphate (LiFePO4), lithium titanate (Li2TiO3), and lithium niobate (LiNbO3).

[0050] (Separator 6) Prior to the negative electrode 5, the separator 6 will be described. The separator 6 is inserted between the positive electrode 4 and the negative electrode 5, and is used for the purpose of insulating the positive electrode 4 and the negative electrode 5. At the same time, since the battery functions by the movement of lithium ions through this separator 6, it is necessary to ensure not only short-term output characteristics but also permeability over a long-term life. The separator 6 is not particularly limited as long as it can ensure insulating characteristics and permeability, and may be a separator 6 for secondary batteries of the prior art, for example, a polyethylene microporous film.

[0051] (Anode 5 and electrolyte 7) Either the negative electrode 5 or the electrolyte 7 contains an Mg-based alloy having an LPSO structure (Long Period Stacking Ordered Structure).

[0052] When the negative electrode 5 contains the Mg-based alloy, the negative electrode 5 uses a lightweight Mg-based alloy matrix, so that a small and lightweight secondary battery 1 that does not use carbon or graphite and is suitable for achieving carbon neutrality can be provided.

[0053] The electrolyte 7 is between the positive electrode 4 and the negative electrode 5 and contains ions that serve as charge carriers. At least a portion of the electrolyte 7 exists as lithium ions, and the lithium ions reversibly move between the two electrodes. When the negative electrode 5 contains the Mg-based alloy, the electrolyte 7 may be a conventional electrolyte 7 for secondary batteries, for example, lithium hexafluorophosphate (LiPF6).

[0054] Here, the electrolyte 7 requires a medium (solvent, etc.) in which at least a part of it dissolves or disperses to form lithium ions. As the medium, an organic polymer medium, for example, a solvent containing ethylene carbonate (EC), is used. However, lithium ion batteries using an organic polymer medium have a risk of ignition. Therefore, it is preferable that the electrolyte 7 is a solid electrolyte, for example, an Mg-Li-YZ alloy having an LPSO structure. Here, Y represents a transition metal element, and Z represents a rare earth element.

[0055] On the other hand, when the electrolyte 7 contains the Mg-based alloy, the negative electrode 5 is not particularly limited as long as it is made of a material different from carbon and graphite. 12 etc.), alloys (Si-(SiO x ), Sn-(SnO x ), Al-(Al x O y ) and Li metal, etc. This makes it possible to provide a small and lightweight secondary battery 1 that does not use carbon or graphite and is suitable for achieving carbon neutrality.

[0056] Hereinafter, one specific example of the negative electrode 5 containing the Mg-based alloy will be described, but the present invention is not limited to this. The Mg-based alloy constituting the negative electrode 5 is preferably an Mg-Li alloy, and the Mg-based alloy preferably contains a transition metal element and a rare earth element. An example of a suitable Mg-based alloy is Mg 78.5 Li 18.0 Y 1.5 Z 2.0 (where Y represents a transition metal element and Z represents a rare earth element), Mg 78.5 Li 18.0 Ni 1.5 Y (Yttrium) 2.0 , Mg 78.6 Li 18.0 Cu 0.7 Ni 0.7 Y (Yttrium) 2.9 etc.

[0057] In this embodiment, whether or not the Mg-based alloy contains a transition metal element and a rare earth element is confirmed using a STEM-HAADF (scanning transmission electron microscope-high angle annular dark field) image and element mapping (EDS mapping).

[0058] By using Mg-Li alloy as the Mg-based alloy, a structure with LPSO structure precipitates surrounding the crystal grains of lightweight α-Mg (hcp structure) and β-Mg (Mg-Li alloy: bcc structure), and β-Mg becomes a deformation absorption site. In addition, by using transition metal elements and rare earth elements as the Mg-based alloy, the interlayer distance of LPSO can be controlled by the type and amount of transition metal elements and / or rare earth elements added to Mg or Mg-Li alloy.

[0059] Fig. 2(A) is a schematic diagram of the state of crystal grains of an Mg-Li alloy. The composition (molar ratio) of the Mg-Li alloy is as shown in Table 1. Here, Y is a transition metal element (Cu: copper) and Z is a rare earth element (Y: yttrium). Also, at% is the composition ratio expressed in atomic percent, which corresponds to the molar ratio. [Table 1]

[0060] In Mg-Li alloys, the LPSO structure precipitates surrounding the lightweight α-Mg (hcp structure) and β-Mg (Mg-Li alloy: bcc structure) crystal grains, as shown in Fig. 2(A). At this time, β-Mg becomes a deformation absorption site.

[0061] Figure 2(B) is a STEM-HAADF (scanning transmission electron microscope - high angle annular dark field) image of the LPSO structure. In the HAADF image, the Y (transition metal element) and Z (rare earth element) enriched phases are observed as white layers.

[0062] Fig. 3 shows the results of STEM microstructure observation of a Mg-Li-Y (transition metal element)-Z (rare earth element) alloy having the composition in Table 1, and Fig. 4 shows element mapping (EDS mapping) of Mg (magnesium (b)), rare earth element Y (yttrium (c)), and transition metal element Cu (copper (d)) in the LPSO structure of the Mg-Li-YZ alloy by energy dispersive X-ray spectroscopy. The EDS mapping shows that the LPSO structure has a composition in which the rare earth element Y and the transition metal element Cu are concentrated in Mg.

[0063] Fig. 5 is a STEM-HAADF image of an LPSO structure obtained by casting an Mg-Li-YZ alloy having the composition shown in Table 1, and Fig. 6 is an enlarged view of a part of Fig. 5. According to Fig. 6, the Mg-Li-YZ alloy is judged to be a 24R-type LPSO phase, in which concentrated phases of Y (transition metal element Cu) and Z (rare earth element Y (yttrium)) periodically appear.

[0064] Fig. 7 shows a STEM-HAADF image of the LPSO structure obtained by casting the Mg-Li-Ni-Y (yttrium) alloy having the composition (molar ratio) in Table 2. At% is the composition ratio expressed in atomic percent, which corresponds to the molar ratio. [Table 2]

[0065] Figure 8 shows a STEM-HAADF image of the LPSO structure obtained by heat-treating the Mg-Li-Cu-Ni-Y (yttrium) alloy having the composition (molar ratio) in Table 3 at 400°C for 100 hours. At% is the composition ratio expressed in atomic percent, which corresponds to the molar ratio. [Table 3]

[0066] 5 to 8, it is experimentally supported that the method for obtaining an LPSO structure from an Mg-based alloy and the composition of the original Mg-based alloy are not particularly limited, and that the LPSO structure may be derived from an Mg-based alloy.

[0067] FIG. 9 is a schematic diagram comparing the crystal framework structure and ion size of lithium manganate used as a positive electrode active material in a full-intercalation type LiB (lithium ion battery).

[0068] Spinel-type oxide Li xMn2O4 (0≦x≦1) has diffusion channels for lithium ions and sites for storing lithium ions, and lithium ions are moved into and out of the lattice positions while maintaining the lattice structure. At that time, the valence of the manganese ions changes between +3.5 when x=1 and +4 when x=0 due to charge compensation.

[0069] The oxide Mn2O4 (x=0), which consists of a +4-valent manganese ion and a lithium vacancy (hole), is called λMnO2 (the space in front of Mn means that the site that stores the lithium ion is a hole), and is used as an electrode material for lithium-ion secondary batteries.

[0070] In addition, both LiMn2O4 and crystals (lambda MnO2) obtained by removing Li from LiMn2O4 have a spinel crystal structure. Regarding "hydroxyl group density as an index of ion exchange capacity of spinel-type manganese oxide lambda MnO2," Non-Patent Document 1 discloses that although the change in their lattice constants varies slightly depending on the preparation method of LiMn2O4, they take roughly similar values ​​as follows: Preparation method 1) LiMn2O4:0.8226nm→λMnO2:0.8038nm Preparation method 2) LiMn2O4:0.8251nm→λMnO2:0.8028nm

[0071] On the other hand, Table 4 shows the values ​​of Li ion radius (unit: nm) disclosed in Non-Patent Documents 2-6. [Table 4] Atomic radius: see non-patent document 2 Ionic radius: see Non-Patent Document 3 Covalent bond radius: see non-patent document 4 Van der Waals radius: see Non-Patent Document 5 Crystal radius: see non-patent document 6

[0072] The ionic radius of Li is estimated to be 0.145 nm and the diameter is estimated to be 0.29 nm, which is about 36% of the lattice constant of λMnO2, which is 0.80 nm. In other words, if the crystal has a framework structure with a lattice constant larger than the diameter of the Li ion, full intercalation is possible.

[0073] The Mg-based alloy may contain a Mg-based high-entropy alloy and / or a Mg-Li-based high-entropy alloy that contains an LPSO structure in at least a part of its structure.

[0074] The mixing entropy ΔS consisting of Mg and at least four elements selected from transition metal elements and rare earth elements, for a total of five or more elements mix Mg-based high-entropy alloys, in which R is 1.5R (R: gaseous number) or more, also have an LPSO structure and exhibit strength properties suitable for use at high temperatures.

[0075] Furthermore, by adding 12 wt% (or 30 at%) or more of Li to the Mg-based high-entropy alloy so as to replace Mg, the thermal workability of the Mg-based high-entropy alloy can be improved. These Mg-based high-entropy alloys and Mg-Li-based high-entropy alloys that contain the LPSO structure in at least a part of their structure are the alloys of the invention described in this embodiment, and are more suitable for use as components of secondary batteries.

[0076] [Battery characteristics] FIG. 10 is a diagram showing the battery characteristics of the lithium ion battery according to the first embodiment, specifically, when a Mg-Li-YZ alloy having an LPSO structure and a composition (molar ratio) shown in Table 1 is used as the negative electrode 5 of the lithium ion battery.

[0077] Here, the change in battery capacity for each number of charge / discharge cycles when charge / discharge is repeated is referred to as battery characteristics. This battery characteristic corresponds to the life of the secondary battery 1, and the less the decrease in battery capacity, the longer the life of the battery. As shown in FIG. 10, the lithium ion battery according to the first embodiment has a gradual decrease in discharge capacity even after 3000 charge / discharge cycles, but no significant decrease is observed. Moreover, the lithium ion battery according to the first embodiment has about 75% of the discharge capacity even after 4000 charge / discharge cycles. In other words, the lithium ion battery according to the first embodiment has sufficient practicality.

[0078] In this embodiment, the secondary battery in which at least one secondary battery component contains an Mg-based alloy having an LPSO structure is described as a lithium ion battery, but is not limited thereto. For example, the secondary battery may be a lithium ion polymer battery, a sodium ion battery, a fluoride ion shuttle battery (fluoride battery), etc.

[0079] <Non-Patent Literature> [Non-Patent Document 1] Tanaka et al., Electrochemistry, vol. 67, No. 10 (1999), 974-978 [Non-patent document 2] BK Vainshtein et al., Structure of Crystals (3rd Edition), (1995) Springer Verlag, Berlin [Non-patent document 3] JCSlater, Journal of Chemical Physics, 39(1964) 3199 [Non-Patent Document 4] Mark Winter, Web Elements, http: / / www.webelements.com / [Non-patent Document 5] A.Bondi, Journal of Physical Chemistry, 68(1964) 441 [Non-patent Document 6] RD Shannon and CT Prewitt, Acta Cryst. B25(1969)925-946 [Industrial Applicability]

[0080] The present invention can provide a small, lightweight secondary battery 1 that does not use carbon or graphite and is suitable for achieving carbon neutrality. [Explanation of symbols]

[0081] 1 Secondary battery 2. Chassis 3 Battery components 4 Positive electrode 5 Negative electrode 6 Separator 7 Electrolytes

Claims

1. A secondary battery, at least one of whose constituent members contains an Mg-based alloy having a LPSO structure (Long Period Stacking Ordered Structure).

2. The secondary battery according to claim 1 , wherein the secondary battery is a LiB (lithium ion battery).

3. The secondary battery according to claim 1 , wherein the secondary battery component is an electrode and / or an electrolyte.

4. 2. The secondary battery according to claim 1, wherein the Mg-based alloy is an Mg-Li alloy.

5. The secondary battery according to claim 1 , wherein the Mg-based alloy contains a transition metal element and a rare earth element.

6. 6. The secondary battery according to claim 1, wherein the Mg-based alloy contains an Mg-based high entropy alloy and / or an Mg-Li-based high entropy alloy having the LPSO structure in at least a part of its structure.

7. An electrode for a secondary battery containing an Mg-based alloy having an LPSO structure (Long Period Stacking Ordered Structure).

8. An electrolyte for a secondary battery, comprising an Mg-based alloy having a LPSO structure (Long Period Stacking Ordered Structure).

Citation Information

Patent Citations

  • Lithium ion battery

    JP1995142089A

  • Lithium secondary battery and its manufacturing method

    JP2001283796A